KONSEP MIX PROGRAMMING DALAM PENCARIAN TIPOLOGI BARU DESAIN TERMINAL BLOK M - Fitriandi Fitriandi; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2022)
Jakarta as the capital of the Unitary State of the Republic of Indonesia is the center of economy and government. The population of DKI Jakarta province continues to grow every year. One of the causes of population growth is urbanization. Population density also differs between the night population and the day population, where the day population is greater due to the presence of commuters. Human density, activity, and the high use of private vehicles cause the city of Jakarta to become one of the cities with the problem of high congestion in the world. As a step in overcoming congestion, the DKI Jakarta government has built a transportation system in the form of TransJakarta buses, MRT, and LRT to invite private vehicle users to switch to using public transportation. But it turns out that it is not optimal without the improvement of other supporting facilities such as transportation buildings. Driving comfort needs to be supported by building comfort that facilitates intermodal movement. Through the cross programming method Bernad Tschumi the author seeks to discover a new typology of the design of a terminal with Blok M Terminal as a case study. Blok M terminal which used to be just a place to transite will be made into a terminal that not only serves as a transit facility but also as a meeting point facility for transportation system users and the surrounding community. Keywords: Transit; Cross Programming ; New Typology; Blok M Terminal AbstrakJakarta sebagai Ibu kota Negara Kesatuan Republik Indonesia merupakan pusat ekonomi dan pemerintahan. Jumlah penduduk Provinsi DKI Jakarta terus bertambah setiap tahunnya. Salah satu penyebab pertambahan penduduk adalah urbanisasi. Kepadatan penduduk juga berbeda antara penduduk malam dengan penduduk siang, dimana penduduk siang lebih besar akibat hadirnya para komuter. Kepadatan manusia, aktivitas, dan tingginya penggunaan kendaraan pribadi menyebabkan kota Jakarta menjadi salah satu kota dengan persoalan kemacetan tinggi dunia. Sebagai langkah dalam mengatasi kemacetan, pemerintah DKI Jakarta telah membangun sistem transportasi berupa bus TransJakarta, MRT, serta LRT guna mengajak pengguna kendaraan pribadi beralih menggunakan kendaraan umum. Namun ternyata hal tersebut belum optimal tanpa peningkatan fasilitas pendukung lainnya seperti bangunan transportasi. Kenyamanan berkendara perlu didukung dengan kenyamanan bangunan yang memfasilitasi perpindahan antar moda. Melalui metode cross programming Bernad Tschumi penulis berusaha untuk menemukan tipologi baru dari desain sebuah terminal dengan Terminal Blok M sebagai studi kasus. Terminal BLOK M yang dahulu hanya sebagai tempat untuk bertransit akan dibuat menjadi sebuah terminal yang tidak hanya berfungsi sebagai fasilitas transit namun juga sebagai fasilitas titik temu bagi pengguna sistem transportasi dan masyarakat sekitar.